Comparison of Consumer Decision Making Styles in Supermarket Consumers of Cargills and Keels Super (With special reference to Western province in Sri Lanka)
Understanding Consumer decision making styles is a vital for marketers in crafting marketing strategies ta best satisfy the target consumers. Market is rapidly growing and consumer is more knowledgeable than the past. Thus the decision making process is more complex in nature. The aim of the present study is to investigate and compare the consumer decision making styles in Cargills and Keels Super supermarket consumers in Western province Sri Lanka. This study used both primary and secondary data. The primary data were collected from the sample survey of 400 Cargi/ls and Keels Super supermarket consumers from Nugegoda, Dehiwala and Colombo areas of Western province. The primary data was collected by administering a structured questionnaire. This study has used Sproles and Kendall’s (1986) Consumer Styles Inventory CS/) and has attempted to examine the generalizability of the scale. Factor analysis has been employed separately to the Cargills and Keels Super samples to summarize the 33 variables identified into smaller sets of linear composites. The results of the exploratory factor analysis have confirmed six factors of original Consumer Styles Inventory CS/). Five factors were found from Keels Super and six factors were found from Cargills. Five consumer decision making styles such as perfectionism, brand conscious, confused by over choice, habitual/brand Joyal conscious and impulsiveness were identical to the both samples. However, in addition to these five decision making styles, recreational conscious was found in Cargills consumers. , number=2, journal=Gyan Management Journal, author=Attanagoda , S.G., year=2013, month=Dec., pages=59–71